2023
DOI: 10.3390/en16031241
|View full text |Cite
|
Sign up to set email alerts
|

Economic and Energetic Assessment and Comparison of Solar Heating and Cooling Systems

Abstract: Solar heating and cooling (SHC) systems are currently attracting attention, especially in times of increasing energy prices and supply crises. In times of lower energy prices, absorption SHC systems were not competitive to compression cooling supported by photovoltaic (PV) modules due to the high investment costs and total energy efficiency. This paper aims to discuss the current changes in energy supply and energy prices in terms of the feasibility of the application of a small absorption SHC system in a mild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In [23] a thorough review and comparison of solar enhanced heating and cooling systems was provided. As a result, the study showed that although solar radiation intensity graphs and cooling consumption graphs have similar profiles, absorption chillers require an extra heat flow that can be provided by natural gas boiler, as was demonstrated in [23]; however, in terms of primary energy usage and the cost of energy, they also suggest the use of heat pumps. To gain even more savings on a primary energy CHP, excess heat can be used.…”
Section: Introductionmentioning
confidence: 99%
“…In [23] a thorough review and comparison of solar enhanced heating and cooling systems was provided. As a result, the study showed that although solar radiation intensity graphs and cooling consumption graphs have similar profiles, absorption chillers require an extra heat flow that can be provided by natural gas boiler, as was demonstrated in [23]; however, in terms of primary energy usage and the cost of energy, they also suggest the use of heat pumps. To gain even more savings on a primary energy CHP, excess heat can be used.…”
Section: Introductionmentioning
confidence: 99%